Design of minimum order equiripple programmable band pass filter for transreceiver circuits. Issue 15 (1st July 2016) - Mehra, P.; Shiwani, S.; Hemrajani, N.; Gupta, R.P.
Abstract : This Letter presents the design of minimum order programmable bandpass filter for transreceiver circuits. The designed filter covers a wide range of 10–40 MHz which covers a variety of digital wireless applications. The wide bandwidth covers multiple wireless standards from TETRA, IS‐95, GSM to TACS. The magnitude responses of the designed filter for various bandwidths are also discussed.